Soviet socialist realism and art in the Asia-Pacific - Carroll, Alison, 1948- (New York, NY : Routledge, 2025)
"This study evaluates how the ideology of Socialist Realism, developed by the Soviets in policies and the practices of art, has been influential in the Asia Pacific region from 1917 until today. Focusing primarily on Russia, then China, Vietnam, Korea, Singapore, Indonesia, the Philippines, and Australia, the book demonstrates how each society adopted and adapted the Soviet example to make some of the most important imagery of recent history. Included is an examination of how the practice of Western art history, the nature of art history in Asia, and the forces of the Cold War have led to this influence being inadequately acknowledged across Asia and more widely. The book is relevant to those interested in art history, Asian studies, political history, and cultural history"--
Art and politics -- Policy and practice -- The art, 1917-1970 -- The art, the 1970s to recent times -- The local.
Keywords: Socialist realism in art -- Pacific Area -- Influence; Art -- Pacific Area -- 20th century; Art -- Pacific Area -- 21st century; Art and society -- Pacific Area -- History -- 20th century; Art and society -- Pacific Area -- History -- 21st century; ART / History / General; ART / Asian; ART / History / Modern (late 19th Century to 1945)